Pengujian Data Hidrologi Dalam Rangka Peningkatan Efektifitas Dan Efisiensi Pengelolaan Sumber Daya Air - Agung Bagiawan; Sri Mulat Yuningsih; Desi Windatiningsih (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2011)
Hydrological data are not only prerequisite for planning, development and management of water resources and the environment, but they are also necessary for the scientific study of hydrological processes. With availability of sophisticated methods for data analysis and multidimensional problems such as floods of long duration, drought, drainage congestion, and low flow in rivers, emphasis is now being placed on comprehensive and quality data. The analysis and use of hydrological data for decision making in water resources planning and management can only be meaningful if the data possess the appropriate characteristics. In general, it is customary that data being analysed are stationary, consistent, free of trend and constituting a stochastic process whose random component is described by an appropriate probability distribution hypothesis. This paper describes, using hypothetical numerical examples where possible, some of the commonly used tests for establishing the presence or otherwise of these attributes in hydrological data series. The tests were then applied to actual streamflow and rainfall data records in upper Cimanuk River Basin. Practical procedures and softwares for quality control of hydrological data have been discussed and developed that may be useful to the users for validating hydrological data.